The Impact of Mobility Models on the Consumption of Network Resources in the Internet of Things (IoT) - Rasha Al-Jarah; Basim Mahmood (Al-Rafidain Journal of Computer Sciences and Mathematics)
Nowadays, the field of Internet of Things (IoT) has become a new trend and one of the most attractive areas of research. It has a wide range of applications; starting from smart devices to developing smart cities. The main issue in this kind of applications is the limitation in network resources (e.g., energy, memory, connectivity, etc.). Most of the works in the literature deal with this issue in a traditional way. For instance, developing routing protocols that find the optimal path for data forwarding. This paper looks to this issue from a different angle. In this work, we aim at testing different mobility patterns and then investigate their impact of the consumption of network resources under particular distributions and data routing protocols. The aspect we aim to investigate and measure is the amount of data exchanged, which in turn affects the power and the memory consumption of a network. We also measure two more aspects; performance stability, and data coverage area. The results show that mobility models play a significant role in the overall network performance.